2015
DOI: 10.1021/acs.jafc.5b02108
|View full text |Cite
|
Sign up to set email alerts
|

NMR Spectroscopy Identifies Metabolites Translocated from Powdery Mildew Resistant Rootstocks to Susceptible Watermelon Scions

Abstract: Powdery mildew (PM) disease causes significant loss in watermelon. Due to the unavailability of a commercial watermelon variety that is resistant to PM, grafting susceptible cultivars on wild resistant rootstocks is being explored as a short-term management strategy to combat this disease. Nuclear magnetic resonance-based metabolic profiles of susceptible and resistant rootstocks of watermelon and their corresponding susceptible scions (Mickey Lee) were compared to screen for potential metabolites related to P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…Currently, NMR-based 1D 1 H spectral comparisons are widely used in plant science and biotechnology field to decipher clues related with economically and commercially significant crops. 1D 1 H-NMR spectroscopy was used to compare the inner and outer cells of catharanthus roseus calli (Yang et al 2009), healthy and infected C. roseus leaves (Choi et al 2004), to distinguish the metabolic profile differences between embryogenic and non-embryogenic callus tissues of sugarcane (Mahmud et al 2014b), to identify the broad range of compounds such as amino acids, carbohydrates, organic acids and phenolic compounds from callus tissue (Palama et al 2010) and to distinguish between metabolic profiles of powdery mildew resistant and susceptible watermelon (Mahmud et al 2014a). Information in this section suggests that the results presented here using 1D 1 H NMR for identifying metabolites from both tissues of M. oliefera can be useful for building an NMR-based metabolite database.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, NMR-based 1D 1 H spectral comparisons are widely used in plant science and biotechnology field to decipher clues related with economically and commercially significant crops. 1D 1 H-NMR spectroscopy was used to compare the inner and outer cells of catharanthus roseus calli (Yang et al 2009), healthy and infected C. roseus leaves (Choi et al 2004), to distinguish the metabolic profile differences between embryogenic and non-embryogenic callus tissues of sugarcane (Mahmud et al 2014b), to identify the broad range of compounds such as amino acids, carbohydrates, organic acids and phenolic compounds from callus tissue (Palama et al 2010) and to distinguish between metabolic profiles of powdery mildew resistant and susceptible watermelon (Mahmud et al 2014a). Information in this section suggests that the results presented here using 1D 1 H NMR for identifying metabolites from both tissues of M. oliefera can be useful for building an NMR-based metabolite database.…”
Section: Resultsmentioning
confidence: 99%
“…This makes 1 H NMR a unique technique, which enables the quantification of compounds in relation to any other compound in the spectrum (Dagnino, Schripsema 2005). Proton ( 1 H) NMR spectroscopy is particularly a good choice in plant metabolomics studies given the universal occurrence of protons in organic metabolites (Kim et al 2007; Mahmud et al 2014a; Mahmud et al 2014b; Palama et al 2010). 13 C NMR was used to characterize triacylglycerols of M. oleifera seed oil to identify oleic-vaccenic acid (Vlahov et al 2002) and the same technique is also used for profiling of glucosinolates and phenolics in vegetative and reproductive tissues of M. oleifera L. and M. stenopetala L (Bennett et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Irrespective of its known functions in animals, the function and mechanism of action of melatonin in plant defense signaling are still not fully understood. Our previous study has shown that melatonin is one of the mobile metabolites translocated from powdery mildew (PM)‐resistant rootstocks (MDR) to susceptible watermelon scions (PMS) in grafted plants . Recently, studies have also shown its role in plant immunity against Pseudomonas syringae pv tomato DC3000 in Arabidopsis and provided evidence of its involvement in plant defense and require salicylic acid (SA) as key downstream component .…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin extraction and detection were carried out using methanol-chloroform-water extractions steps based on previous reports. 70,71 In summary, 20 mg of freeze-dried, homogenized leaf tissues was extracted using constant solvent volume of methanol:chloroform:water::2:2:1.8 ratio according to Bligh and Dryer method. 72,73 The freeze-dried leaf samples were rehydrated using ice-cold methanol/water mixture.…”
Section: Melatonin Extraction and Detectionmentioning
confidence: 99%
“…Visual inspection of the PCA scores plots provided the completely separate clusters for two groups of spectra as well as computation of the Mahalanobis distance (D M ) also provided a convenient metric to quantitatively compare the magnitude of cluster separation[17]. PCA scores plots allowed discriminating pattern among control and experimental samples in various plant biotechnology research[1921]. Each data point in a score plot represents all extracted metabolites present in one sample; therefore, the separations between the grouped metabolic profiles can be based on individual metabolites.…”
Section: Resultsmentioning
confidence: 99%